Bahasa Inggris Bahasa Inggris - Arfiananda, Salsabila Intan Nur; AS, Fathor; Islam, Darul (Universitas Muhammadiyah Pontianak, 2026)
This study explores the strategic role of destination image in shaping tourist experiences and behavior at the Tomb of Syaichona Cholil. Using PLS-SEM with 97 tourists, it examines how community participation, authenticity, and local product access influence satisfaction and trust. Results show all destination image dimensions significantly affect satisfaction. Community participation and product access strongly impact trust, while authenticity has a weaker but positive effect. Satisfaction mediates the relationship between destination image and trust, highlighting its central role in enhancing tourist behavioral responses in religious tourism settings.